Healthcare workers attitude towards SARS-COVID-2 Vaccine, Ethiopia - Bereket A Guangul; Georgiana Georgescu; Mensur Osman; Rebecca Reece; Zinabu Derso; Aliyu Bahiru; Ziteste B Azeze (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2021)
Background: The COVID-19 vaccine pandemic is expected to control the pandemic. The vaccine acceptance in Africa is yet unknown. This survey was conducted to explore attitudes of healthcare workers towards COVID-19 vaccine and predictors of negative attitude.  Materials and methods: A cross sectional online survey was performed among 1110 healthcare workers to understand COVID-19 vaccine acceptability, encouragement of patients to take COVID-19 vaccine, encouragement of family members to take COVID-19 vaccine, and fears/concerns about COVID-19 vaccine. COVID-19 vaccine acceptance was compared across demographic variables and COVID-19 vaccine attitudes. Results: The response rate was 60.2%. Out of the 668 respondents, substantial majority were physicians 49.4% and nurses 32.9 %. The vaccine acceptance rate was 72.2% (482/668). Only about 64 % reported that they would encourage their patients or families to get vaccinated. Those who reported they would accept the vaccination were highly likely to encourage their family members to be vaccinated (OR 58.13, 95 % CI 9.7 - 348.32, P 0.001) over those who reported they would not encourage their family to be vaccinated. Majority (77%) had one or more fears/concerns about the COVID-19 vaccine. Among the fears/concerns were vaccine adverse reaction, effectiveness of the vaccine, vaccine was made too fast to be safe, and COVID-19 from the vaccine.  Conclusion: The high vaccine hesitancy rate (27.8%) among healthcare workers in Ethiopia is genuinely concerning. Healthcare workers are the main source of health-related information for their communities. Thus, we need to equip them with the most accurate and credible knowledge to increase COVID-19 acceptance in Ethiopia.